Toward a Framework for Computer-Mediated Collaborative Design in Medical Informatics - Patel, V.L.; Kaufman, D.R.; Allen, V.G.; Shortliffe, E.H.; Cimino, J.J.; Greenes, R.A. (Methods of Information in Medicine, 1999)
The development and implementation of enabling tools and methods that provide ready access to knowledge and information are among the central goals of medical informatics. The need for multi-institutional collaboration in the development of such tools and methods is increasingly being recognized. Collaboration involves communication, which typically involves individuals who work together at the same location. With the evolution of electronic modalities for communication, we seek to understand the role that such technologies can play in supporting collaboration, especially when the participants are geographically separated. Using the InterMed Collaboratory as a subject of study, we have analyzed their activities as an exercise in computer- and network-mediated collaborative design. We report on the cognitive, sociocultural, and logistical issues encountered when scientists from diverse organizations and backgrounds use communications technologies while designing and implementing shared products. Results demonstrate that it is important to match carefully the content with the mode of communication, identifying, for example, suitable uses of E-mail, conference calls, and face-to-face meetings. The special role of leaders in guiding and facilitating the group activities can also be seen, regardless of the communication setting in which the interactions occur. Most important is the proper use of technology to support the evolution of a shared vision of group goals and methods, an element that is clearly necessary before successful collaborative designs can proceed.
Keywords: Computer-Mediated Collaboration; Clinical Guidelines; Distributed Cognition; Communication Technologies; Internet-based Collaboration